Respuesta :
Hello!
The correct option is:
C. [tex]2(y+1)+y=7[/tex]
Why?
To find which of the given options are not the result of a substitution in the given system, we need to isolate the variable in function of the other variable, and then substitute it.
So, substituting and discarding, we have:
- First equation:
[tex]2x+y=7[/tex]
Isolating "y", we have:
[tex]y=7-2x[/tex]
Then, substituting it into the second equation, we have:
[tex]y-x=1[/tex]
[tex]7-2x-x=1[/tex]
We have that it's a result of a substitutiong in the following system (option A)
- Second equation:
[tex]y-x=1[/tex]
Isolating "y", we have:
[tex]y=x+1[/tex]
Then, substituting it into the first equation, we have:
[tex]2x+y=7[/tex]
[tex]2x+(x+1)=7[/tex
[tex]2x+x+=7[/tex
We have that it's a result of a substitution in the following system (option B)
Hence, we have that the option C is not a result of a substitution in the given system of equations since there is not a possible value of the variable "x" that is equal "y+1".
So, the correct option is:
C. [tex]2(y+1)+y=7[/tex]
Have a nice day!